FIKIH LINGKUNGAN HIDUP; UPAYA PELESTARIAN LINGKUNGAN DALAM ISLAM - Faiz Zainuddin (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2024)
Fiqh as Islamic law that regulates the pattern of human relations with God and with each other, takes part in discussing the relationship between humans and their environment. This research examines environmental fiqh issues. With the aim of formulating environmental jurisprudence that is comprehensive, systematic and accountable and able to deal with the problem of global warming. Where in the data analysis with descriptive qualitative research. And the data collection technique is a library or library research. In this study it was concluded that fiqh contributes to the problem of efforts to maintain environmental harmony by providing rules or codes of ethics for human relations with their environment. Such as the prohibition of destroying the environment and the obligation to preserve the environment. This arrangement of environmental law is based on tafsiliy arguments, namely the Qur'an-al-Hadith, and the general principles of legal legislation. When jurisprudence takes part in environmental preservation, it is hoped that there will be a new awareness for all Muslim leaders, especially awareness related to environmental issues. They have high concern for the environment